Desenho e an??lise de grades quase-peri??dicas tipo Fibonacci para o acoplamento ??ptico entre fibras ??pticas e guias de onda - Picin, Odair Jos?? (2020)
Grid couplers have become a key element in converting optical-to-electronic (electronic-to-optical) signals into communication systems using optical fibers and waveguides. Although this interest has motivated considerable progress in recent years, with a variety of proposals in the literature, its implementation remains limited due to the principle of operation. In particular, grids are conventionally designed using the Bragg principle, which ends by limiting operation to a specific wavelength (frequency). In this work, we present a new concept of grid coupler, called a quasi-periodic grid, with which we not only achieve a broadband coupling response, but also the coupling for multiple wavelengths in the region of frequencies of interest. The unit cell of each structure was designed following the Fibonacci sequence to control the degree of disorder in the structure. All of our results were obtained using the finite difference in the time domain method (FDTD), with simulations performed in the commercial software Lumerical FDTD Solution. It is hoped that our proposal can lead to the development of platforms that allow to meet the growing market demand for greater capacity and bandwidth in optical communications.